Mitigation of allelopathic effects of Empetrum nigrum on grass species by Andosol soil in comparison with non-volcanic soils - Jóhanna Friðsemd Kristinsdóttir 1998- (2024)
Allelopathy is a mechanism in which plants release compounds into their environment that subsequently causes harmful effects to other organisms. The dwarf shrub Empetrum nigrum L is a species of interest in allelopathy and has been extensively studied in mainland Scandinavia as been shown to inhibit the early development of various plant species, especially fast growing herbaceous plants and affect associated soils. In the central highlands of Iceland, ecosystems are degraded due to high grazing pressures and recover slowly when protected from grazing. The allelopathic activity of Empetrum may contribute to its slow recovery. However, our understanding of Empetrum’s role in Icelandic ecosystems is limited. Icelandic ecosystems are characterized by volcanic soils, primarily Andosols, which vary significantly from non-volcanic soils in mainland Scandinavia. As a result, the allelopathic effects of Empetrum might be different in Icelandic soils compared to non-volcanic soils in mainland Scandinavia. This study is a step towards a better understanding that role by asking whether the allelopathic impact of Empetrum leaves are mitigated by Empetrum-associated soils and if the Andosols differ in that respect from non-volcanic soils. To address the research question, I conducted a bioassay experiment using Empetrum-associated Andosols from a highland site in Auðkúluheiði and non-volcanic soils from Northern-Norway and the Faroe Islands. The experiment involved evaluating the root elongation and seed germination Festuca richardsonii seeds, a fast-growing grass species in Iceland. The seeds were tested in all soils under two conditions: with and without the addition of Empetrum leaves. The germination and root elongation of F. richardsonii seeds were not affected by Empetrum-associated soils alone, contrary to predictions. Interestingly, all soils mitigated the inhibiting effects of Empetrum leaves on seed germination but no root elongation. However all soils mitigated the effects of Empetrum on both root elongation and ...